An update on Bayesian updating - Holt, Charles A.; Smith, Angela M. (Journal of economic behavior & organization, 2009)
This paper reports an experiment in which subjects are asked to assess probabilities for unknown events, with treatments that vary the extremity of the prior information. Probabilities are elicited using a Becker–DeGroot–Marshak procedure that does not depend on assumptions about risk aversion. The focus is on the pattern of biases in information processing.